Pengaruh Green Product, Green Price, Green Place, dan Minat Beli Terhadap Keputusan Pembelian Produk Pepsodent (Studi Kasus Mahasiswa Prodi Manajemen Unisma Angkatan 2019) - Machfud Al Amin; Agus Widarko; Muhammad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of green product, green price, green place, and purchase intention on purchasing decisions for Pepsodent products. The type of research used is descriptive using a quantitative approach. The population in this study were Pepsodent consumer customers from Unisma Management Study Program students class of 2019 with a sample of 85 respondents. This study used a purposive sampling method with multiple linear regression analysis techniques. The results of this study indicate that: (1) Green Product has a significant positive effect on purchasing decisions. (2) Green Price has no effect and is not significant on purchasing decisions. (3) Green place has a significant positive effect on purchasing decisions. (4) Buying interest has a significant positive effect on purchasing decisions.  Keywords: Green Product, Green Price, Green place, Purchase Intention to Purchase Decision